Method for producing a single layer lithium ion battery separator

A non-woven fabric battery separator with microfibers and nanofibers, produced via a wet deposition process, addresses the limitations of existing separators by providing high tensile strength, low permeability, and controlled pore size, enhancing battery performance and safety through precise manufacturing adjustments.

JP7623011B2Active Publication Date: 2025-01-28DREAMWEAVER INTERNATIONAL INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2022175953
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2011-05-20
Filing Date
2022-11-02
Publication Date
2025-01-28
Estimated Expiration
2032-05-18

AI Technical Summary

Technical Problem

Existing battery separators lack the ability to provide high tensile strength, low permeability, and controlled pore size while maintaining dimensional stability and ease of manufacturing, which are crucial for ensuring long-term battery performance and safety.

Method used

A single-layer polymer battery separator composed of a non-woven fabric containing microfibers and nanofibers, produced through a wet deposition process, allowing for precise control of pore size and permeability by adjusting the ratio and distribution of microfiber and nanofiber concentrations.

Benefits of technology

The solution provides a battery separator with enhanced tensile strength, controlled pore size, and reduced permeability, enabling efficient ion transport, improved battery performance, and safety against electrode contact, while allowing for easy manufacturing and customization to meet specific battery requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007623011000007
    Figure 0007623011000007
  • Figure 0007623011000008
    Figure 0007623011000008
  • Figure 0007623011000009
    Figure 0007623011000009
Patent Text Reader

Abstract

To provide a battery separator that simultaneously provides low air resistance and small pore size, and has high tensile strength at an overall and relatively isotropic level, while providing adequate chemical stability, structural integrity, dimensional stability, and ease of manufacture. [Solution] A polymeric battery separator comprising a nonwoven fabric blend of microfibers and nanofibers, wherein the nanofibers have an average diameter of less than 1000 nm, the microfibers have a diameter greater than 3000 nm, and the nanofibers and microfibers are intermixed, thereby forming a single layer separator whereby at least a portion of the nanofibers reside in the gaps between the microfibers.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to insulating (non-conductive) microporous polymer battery separators composed of a single layer of entangled microfibers and nanofibers. Such separators provide the ability to tailor porosity and pore size to any desired level throughout a single nonwoven fabric. As a result, the separators of the present invention allow for high strength materials with previously unachieved low levels of porosity and small pore sizes. The incorporation of polymer nanofibers within a matrix of polymer microfibers and / or on such supports via high shear processing also provides such benefits. Separators, batteries containing such separators, methods of making such separators, and methods of using such separators in battery devices are all encompassed by the present invention. [Background technology]

[0002] Batteries have been used for many years as power generators in remote locations. The controlled movement of electrolyte (ions) between electrodes (anode and cathode) creates a power circuit, providing a source of electricity that can be used until the electrolyte supply is depleted and no further electricity can be generated. In recent years, rechargeable batteries have been invented, allowing for longer life for such remote power sources, but still require such batteries to be connected to another electrical source for a period of time. Generally speaking, however, the ability to reuse such batteries has provided great potential for use, particularly in mobile phones and laptop computers, and even automobiles that require only electricity to function.

[0003] Such batteries typically have at least five separate components. A case (or container) contains everything in a safe and reliable manner to prevent leakage to the outside and exposure to the environment inside. Inside the case are the anode and cathode, effectively separated by a separator, and an electrolyte solution (a low viscosity liquid) that transports across and / or through the separator between the anode and cathode. Today's and perhaps future rechargeable batteries will run all of the fairly small and portable devices, but with the potential to generate significant amounts of electricity to be effective for the long periods between charging times for the fairly large number of types of items found inside an automobile, such as large electrodes (at least in terms of surface area) that must not touch each other, and large amounts of electrolyte that must continually and constantly pass through a membrane to complete the necessary circuits, all at a level that generates enough power to help provide enough electricity to run an automobile's engine. Thus, the performance and capabilities of future battery separators must meet certain requirements that are not yet provided by the current industry.

[0004] Generally speaking, battery separators have been used since the advent of closed cell batteries to provide the necessary protection from undesired contact between the electrodes and to effectively transport the electrolyte within the battery to generate electrical power. Typically, such materials are of thin film construction, thin enough to reduce the weight and volume of the battery device, while at the same time providing the necessary properties mentioned above. Such separators must also provide other properties and allow proper battery function. These include chemical stability, adequate porosity for ionic species, effective pore size for electrolyte transport, adequate permeability, effective mechanical strength, and the ability to maintain dimensional and functional stability when exposed to high temperatures (and against potential failure if the temperature rises to an abnormally high level).

[0005] Now, more specifically, the separator material must have sufficient strength and structure to withstand many different scenarios. First, the separator must not tear or be punctured under the stresses of assembling the battery. In this sense, the overall mechanical strength of the separator is crucial, and in particular, a material with high tensile strength in both the longitudinal and transverse (i.e., cross) directions allows manufacturers to handle such separators easily and without strict guidelines to ensure that the separator does not suffer structural failure or loss during such critical steps. Furthermore, from a chemical standpoint, the separator must be able to withstand the oxidizing and reducing environment within the battery itself (especially when fully charged). Any failure during use, particularly with respect to structural integrity, would allow an abnormal amount of electrolyte to pass through or allow the electrodes to come into contact, thus destroying the power generation capability and rendering the battery completely ineffective. Thus, beyond performance against climatic and chemical exposure, such separators must not lose dimensional stability (i.e., warp or melt) or mechanical strength during storage, manufacture, and use for reasons similar to those stated above.

[0006] But at the same time, the separator must have the proper thickness to facilitate the high energy and power density of the battery itself. Uniform thickness is also very important to enable long cycle life, and any uneven wear on the separator will result in insufficient connection for proper electrolyte passage and protection for electrode contact.

[0007] Moreover, such separators must exhibit appropriate porosity and pore size consistent with proper transport of ions through such membranes (and with adequate capacity to retain a certain amount of liquid electrolyte to facilitate transport of such ions during use). The pores themselves must be small enough to prevent elements of the electrodes from penetrating and / or passing through the membrane, while allowing an adequate rate of electrolyte ion migration, as discussed above. Furthermore, as discussed above, uniformity of pore size and pore size distribution provides uniform generation of power over time as well as reliable long-term stability for the entire battery, such that uniform wear on battery separators, at least when best controlled in such systems, allows for long cycle life. In addition, it would be advantageous to ensure that the pores therein close appropriately when exposed to abnormally high temperatures, thereby preventing excessive and undesirable ion migration when the battery is damaged (i.e., protecting against fire and other similar hazards).

[0008] Additionally, the pore size and distribution may increase or decrease the air resistance of the separator, which is simply a dimension of the separator that indicates its ability to adequately pass electrolyte present in the battery itself. For example, the mean flow pore size can be measured according to ASTM E-1294, and this dimension can be used to help measure the barrier properties of the separator. That is, when the pore size is small, the rigidity of the pores themselves (i.e., the ability of the pores to maintain a constant size over time and when exposed to a set pressure) also allows for effective control of the separation of the electrodes. Perhaps more important is the ability of such pore size levels to limit the permeability of the electrolyte to reduce the opportunity for crystals to form on the anode (e.g., lithium crystals on a graphite anode), which would impair the formation of the necessary circuits and adversely affect the power generation ability of the battery over time.

[0009] Furthermore, the separator must not impair the ability of the electrolyte to fully saturate the entire battery during manufacture, storage, and use; that is, the separator must be adequately absorbent and / or wettable at those stages to ensure that the electrolyte actually generates ions properly and transfers ions through the membrane. If the separator is not conductive in such a situation, the electrolyte cannot be adequately present on and in the separator, and the necessary ionic transfer will not, at least in theory, occur easily.

[0010] In this case, the general objective of an effective battery separator is to have low air resistance and at the same time a very small pore size in order to provide a material that drastically reduces any possibility of electrodes touching, but has the ability to control the movement of electrolyte from one location in the battery cell to the other (i.e., to close the circuit to generate the necessary power). Currently, these properties have not been effectively provided at the same time. For example, Celgard has released and sells an expanded film battery separator with a very small pore size, which is very good in the above-mentioned respects, but the corresponding air resistance for such a material is very high, thus limiting the overall effectiveness of such a separator. In contrast, duPont has marketed a nanofiber nonwoven membrane separator that provides very low air resistance, but its pore size is very large. Furthermore, the overall mechanical strength exhibited by these two materials is very limited. Celgard separators have excellent strength in the machine direction, but almost zero strength in the cross direction (transverse direction). Such low transverse strength, at least in the respects mentioned above, requires very delicate handling in manufacturing. The DuPont material is somewhat better, except that its strength is considerably lower in both directions, and has a higher transverse strength than the Celgard material. In fact, the DuPont product is closer to an isotropic material (a material with roughly the same strength in both the longitudinal and transverse directions), and therefore is a more reliable material in terms of handling than the Celgard type. However, the measured tensile strength of the DuPont separator is actually quite low, and thus users are still forced to handle and install the material carefully in manufacturing. Similarly, the dimensional stability of these prior art battery separators is quite questionable due to these tensile strength problems, and over long periods of time when in a rechargeable battery cell, the material may undesirably lose structural integrity. Summary of the Invention [Problem to be solved by the invention]

[0011] Thus, there remains a need to provide a battery separator that simultaneously provides low air resistance and small pore size, and also has high tensile strength at an overall and relatively isotropic level, while providing adequate chemical stability, structural integrity, dimensional stability, and ease of manufacture. Furthermore, a method for producing a battery separator that allows for the achievement of targeted property levels (such as a specific range of pore size and / or a specific range of measured air resistance) with minor manufacturing changes would provide great versatility to meet the needs of battery manufacturers, but currently such a manufacturing method has not been sought throughout the battery separator industry. Thus, a method for producing a battery separator that is effective and fairly simple and easy to use with respect to providing such a versatile end result (i.e., targeted porosity and air resistance levels with processing changes on demand) and any number of membranes exhibiting the required levels of mechanical properties, heat resistance, permeability, dimensional stability, arrestance properties, and melting properties would be highly valued in the rechargeable battery separator industry, but such materials are not available. [Means for solving the problem]

[0012] A distinct advantage of the present invention is the ease of manufacture by wetlaid nonwoven fabric fabrication processes. Another distinct advantage is the final properties that provide targeted levels of pore size, porosity and air resistance by simply changing the ratio of constituent fibers used during the fabrication process. Yet another advantage of the battery separator of the present invention is the isotropic strength properties that provide reliability to users during long term use as well as during the manufacturing stage of the battery. The ability of the separator of the present invention to simultaneously provide low air resistance and small pore size is a further advantage of the present invention. Yet another advantage of the battery separator of the present invention is that it provides a particularly non-conductive (i.e. insulating) fabric that does not transfer charge through the separator body, but simply transports charged ions through the pores present in its structure. Yet another advantage is the high porosity of the material, which allows more electrolyte to flow and increases durability in terms of the ability of the electrodes to be fully recharged and thus retain energy over many cycles of use.

[0013] Thus, the present invention resides in an insulating polymer battery separator comprising a nonwoven blend of microfibers and nanofibers, which provides sufficient porosity for electrolyte ion passage and adequate protection against electrode contact through a single layer of said nonwoven blend. A battery having such an insulating separator and a method of using such a battery to generate electricity in a rechargeable device are also included in the present invention. Furthermore, the present invention also includes a method of manufacturing an insulating polymer battery separator by a wet-laid nonwoven fabrication process, in which a multiplicity of polymer microfibers of at least one polymer component or a multiplicity of polymer nanofibers of at least one polymer component or both said multiplicity of polymer microfibers and nanofibers are combined in a high shear environment, thereby forming a slurry of a multiplicity of fibrillated polymer microfibers and a multiplicity of nanofibers, from which a single layer of fabric is formed.

[0014] Throughout this specification, the term microfiber is intended to mean any polymer fiber having a width on the scale of micrometers, which generally has a fiber diameter of more than 1000 nm, or more than 3000 nm, or more than 5000 nm, or more than 10000 nm, and not more than about 40 microns. Similarly, the term nanofiber is intended to mean any polymer fiber having a width on the scale of nanometers, which generally has a diameter of less than 1000 nm, or less than 700 nm, or less than 500 nm, or less than 300 nm (as small as about 1 nm). Similarly, the term insulating is intended to not indicate any significant degree of electrical conductivity, and thus the fabric structure of the present invention does not pass charge throughout the fabric body, but only allows electrolyte ions to pass through the pores present therein.

[0015] Such combinations of microfibers and nanofibers have not yet been explored in the field of battery separators, and in particular the possibility of providing a single layer nonwoven fabric of the two basic components for such purposes. The microfiber component may be any suitable polymer that provides the necessary chemical and thermal resistance as described above, and also has the ability to form a microfiber structure. Similarly, such microfibers may be fibrillated during or after fiber formation (or treated in any other similar manner, such as exposure to plasma or other similar treatments) in order to increase their surface area and facilitate the desired degree of entanglement of a multiplicity of these microfibers with each other during the process of fabricating the nonwoven fabric. Such polymeric components may include acrylics (e.g., polyacrylonitrile), polyolefins (e.g., polypropylene, polyethylene, polybutylene, and others including copolymers), polyamides, polyvinyl alcohol, polyethylene terephthalate, polybutylene terephthalate, polysulfones, polyvinyl fluoride, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polymethylpentene, polyphenylene sulfide, polyacetyl, polyurethanes, aromatic polyamides, semi-aromatic polyamides, polypropylene terephthalate, polymethyl methacrylate, polystyrene, and blends, mixtures, and copolymers of these polymers. Polyacrylates, polyesters, and polyolefins are perhaps preferred.

[0016] The fibers may be pretreated with adhesives to provide the desired degree of contact and dimensional stability of the entire nonwoven structure after fabrication. The nanofibers may be of any similar polymeric composition so that they can withstand exposure to the same types of chemicals and high temperatures as the microfibers. Due to the size of the nanofibers, no post-fabrication treatment is required for such nanofiber materials to provide increased entanglement on the surface or within the interstices of the fabricated nonwoven. However, what is important is that the nanofibers must be combined with the microfibers under a sufficiently high shear environment to provide the desired incorporation of the nanofibers on and within the resulting microfiber nonwoven support at the same time as fabricating the actual nonwoven itself. In other words, when providing both types of fibrous materials in the nonwoven fabric fabrication process, the manufacturer should provide a sufficient amount of mixing and high shear conditions to best create the appropriate degree of entanglement between the different types of fibers, thereby forming the desired single-layered fabric structure. Similarly, in addition to the high shear type, fabrication methods such as wet-laid nonwoven processes are likely desirable to ensure proper incorporation and retention of the nanofibers within the interstices of the microfibers. Increasing the flow of water during production will result in a greater proportion of extremely small nanofibers being entrapped in these interstices than would be possible using dry entanglement methods, thereby providing the gap-filling capabilities described above. The resulting nonwoven structure will exhibit greater uniformity in terms of thickness, porosity, and most importantly, pore size.

[0017] In one such method according to the wet-laying method, prefibrillated microfibers are provided in a pulp-like composition, which comprises, for example, up to about 80% by weight of an aqueous composition (water alone is preferred, but other solvents that allow the wet-laying process and facilitate subsequent evaporation can be used, including, for example, certain non-polar alcohols). Prefibrillated microfibers processed in such a manner have a certain amount of already present nanofibers (which are residual products that are removed from the microfibers themselves during fibrillation, but are not subsequently removed from the bulk of the microfiber mesh). The prefibrillated fibers are pulp-like as a result of the fibrillation process, resulting in a slurry-like composition comprising the above-mentioned aqueous solvent with prefibrillated microfibers and nanofibers. This slurry formulation is then mixed with a selected amount of other microfibers and / or nanofibers (preferably also in pulp or slurry form), and this formulation, with a very low concentration of actual fiber solids (i.e., 90% or more by weight water or other aqueous solvent), is then placed on a flat surface and subjected to a high shear environment. The surface is sufficiently porous to allow the solvent to dissolve, thus resulting in a single layer of fabric that is the desired wet-laid nonwoven comprising intertwined fibrillated microfibers, with gaps between each microfiber, and nanofibers present within the gaps and on the surfaces of the larger microfibers. The amount of nanofibers added to the prefibrillated microfiber pulp allows it to be highly packed between the gaps of the microfibers, resulting in an overall small average pore size, especially when compared to wet-laid nonwovens made solely from prefibrillated pulp alone. Conversely, then, the addition of microfibers to a prefibrillated fiber slurry will result in a resulting wet laid nonwoven single layer fabric with a larger average pore size than the prefibrillated fiber slurry alone.This ability to target different average pore sizes with nanofiber and / or microfiber loading gives the manufacturer the possibility to achieve any desired average pore size level. Also, the possibility to calendar or vary the thickness of the resulting single layer fabric gives the manufacturer even greater possibilities in terms of both air resistance and average pore size dimensions. Such a dial-in process has not yet been explored in the battery separator industry.

[0018] Other methods of producing nonwoven sheets that allow for the entanglement of a combination of nanofibers and microfibers can also be used to fabricate the battery separator of the present invention. One method would be to start with separate nanofibers and microfibers and combine them in the manner described above. Other such methods include carding, cross-lapping, hydroentangling, airlaid, needle punching, or other methods that can form an entangled mesh with microfibers and nanofibers that fill the gaps between the microfibers.

[0019] As mentioned above, the gaps between the microfibers actually form the "pores" themselves, and the nanofibers fill these openings, reducing their size, to a substantially uniform extent throughout the nonwoven structure. A wholly unexpected benefit of the present invention as a whole is the ability to tailor the pore size in the resulting nonwoven structure, particularly with respect to targeting different levels of porosity on demand, by simply varying the concentrations of microfibers and nanofibers alone. Thus, for example, a ratio of 70% microfibers and 30% nanofibers in the initial nonwoven fabrication process will result in a pore size range of L to M, while a combination of 60% microfibers and 40% nanofibers will effectively provide a small pore size distribution (with the range being more uniform). Thus, such an unexpected result, as mentioned above, allows for a fairly simple manufacturing change to provide a tailored pore result for the end user. The resulting pore size can then be measured, and the mean flow pore size obtained. Such mean flow pore sizes will be less than 2000 nm, or even less than 1000 nm, preferably less than 700 nm, and more preferably less than 500 nm.

[0020] However, the manufacturer also has other means to control the desired properties of the battery separator of the present invention by setting the various thicknesses of the monolayer structure as required. Such thickness properties may be set solely by the process parameters of the initial wet-laid fabrication method, or the manufacturer may later calendar the resulting fabric to any desired thickness. Such thicknesses will be less than 250 micrometers, preferably less than 100 micrometers, more preferably less than 50 micrometers, more preferably less than 35 micrometers, and most preferably less than 25 micrometers. As mentioned above, the ability to prevent contact between the anode and cathode of the battery is necessary to prevent short circuits during use of the battery, and the thickness of the separator and controlled pore size therein provide an important means to achieve such a result. However, the thickness of the battery separator may also affect the available volume of other components in a closed battery cell, as well as the amount of electrolyte solution provided therein. The totality of these related circumstances requires a separator that is effective with respect to a number of variables. Thus, the advantageous ease of manufacture and ability to provide effective pore size and air resistance properties on demand with the manufacturing method of the present invention and the single layer battery separator produced thereby distinguishes this development from state of the art battery separators currently in use and sold.

[0021] In addition, a single-layer separator containing both microfibers and nanofibers is disclosed in this invention. It should be noted that, although it is encompassed within the express scope of the present invention, the use of multiple layers of such fabric structures, or the use of multiple layers consisting of a single layer of the battery separator fabric of the present invention and at least one other layer of another type of fabric, may also be employed and are within the overall scope of the invention described herein.

[0022] The battery separators described herein are clearly useful for improving primary and rechargeable battery technology, but may also be used for other forms of electrolytically conductive energy storage technology, such as capacitors, supercapacitors, and ultracapacitors. Indeed, the control possible over the pore size of the separators of the present invention may allow for significant improvements in the energy loss, charge rate, and other properties of these devices. [Brief description of the drawings]

[0023] [Figure 1] FIG. 1 is an SEM micrograph of a prior art expanded film battery separator. [Diagram 2] FIG. 2 is an SEM micrograph of a prior art nanofiber nonwoven battery separator. [Diagram 3] FIG. 3 is a SEM micrograph at 3000X of one possibly preferred embodiment of a microfiber / nanofiber nonwoven battery separator structure of the present invention. [Figure 4] FIG. 4 is a SEM micrograph at 15,000X of one possibly preferred embodiment of a microfiber / nanofiber nonwoven battery separator structure of the present invention. [Diagram 5] FIG. 5 is a SEM micrograph at 2000X of another possibly preferred embodiment of a microfiber / nanofiber nonwoven battery separator structure of the present invention. [Figure 6] FIG. 6 is an SEM micrograph at 2000X of another possibly preferred embodiment of a microfiber / nanofiber nonwoven battery separator structure of the present invention. [Figure 7] FIG. 7 is a SEM micrograph at 2000X of another possibly preferred embodiment of a microfiber / nanofiber nonwoven battery separator structure of the present invention. [Figure 8]FIG. 8 shows an exploded view of a rechargeable lithium ion battery of the present invention including a battery separator of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] All the features of the present invention and its preferred embodiments will now be described in greater detail in connection with the following illustrative, but non-limiting, figures and examples.

[0025] Microfiber and nanofiber manufacturing As indicated above, the microfibers can be composed of any polymer (or polymer blend) that provides suitable chemical and thermal resistance in conjunction with the internal battery cell conditions, and also provides the ability to form suitable fibrous structures within the ranges set forth herein, as well as the possibility of processing by fibrillation or similar techniques to increase the surface area of ​​the fibers themselves for ease of entanglement in fabricating nonwoven fabrics. Such fibers can be produced by conventional fiber manufacturing methods such as melt spinning, wet spinning, solution spinning, melt blowing, and other methods. Additionally, such fibers can start as bicomponent fibers and can be reduced or modified in size and / or shape by further processing, such as splittable pie fibers, islands-in-the-sea fibers, and the like. Such fibers can be cut to suitable lengths for further processing, which may be less than 1 inch, or less than 1 / 2 inch, or even less than 1 / 4 inch. Such fibers may be fibrillated into smaller fibers or may be fibrillated into fibers that are advantageous for forming wetlaid nonwoven fabrics.

[0026] Nanofibers for use in the present invention can be produced by several conventional techniques, such as islands-in-the-sea technology, centrifugal spinning, electrospinning, fibrillation of films or fibers, and the like. Teijin and Hills have both marketed the preferred islands-in-the-sea nanofibers (Teijin's is marketed as NanoFront fiber, a polyethylene terephthalate fiber having a diameter of 70 nm). Dienes and FiberRio both market equipment for producing nanofibers using centrifugal spinning technology. Production of nanofibers by electrospinning has been carried out by duPont, E-Spin Technologies, or in equipment marketed for this purpose by Elmarco. Nanofibers fibrillated from films are disclosed in U.S. Patents 6,110,588, 6,432,347, and 6,432,532, which are incorporated herein by reference in their entireties. Nanofibers fibrillated from other fibers can be made so by high shear grinding processes. Nanofibers made from fibrillated cellulose and acrylic fibers are commercially available under the trade name EFTEC® from Engineered Fiber Technologies. Any of these nanofibers can be further processed by cutting and high shear slurry processing to separate the fibers, which can then be subjected to wet-laid nonwoven processing. Such high shear processing can be done with or without the presence of the required microfibers.

[0027] Generally, nanofibers produced by fibrillation have a transverse aspect ratio that differs from that detailed in U.S. Patent No. 6,110,588, which is incorporated herein by reference. Thus, in one preferred embodiment, the nanofibers have a transverse aspect ratio greater than 1.5:1, preferably greater than 3.0:1, and more preferably greater than 5.0:1.

[0028] Thus, acrylic, polyester and polyolefin fibers are particularly preferred for such purposes, with fibrillated acrylic fibers perhaps most preferred, but again, this is presented merely as an indication of one possibly preferred type of polymer for this purpose and is not intended to limit the scope of possible polymeric materials or polymer blends for such purposes.

[0029] Figures 1 and 2 show micrographs of typical structures of the Celgard foamed film material and the duPont nanofiber nonwoven battery separator material mentioned above, respectively. Clearly, the film structure of the Celgard separator shows similarities in pore size, and is clearly all formed by film extrusion, thereby exhibiting a surface that is broken down into a fairly uniform configuration. The duPont separator is made strictly from nanofibers, and the uniformity of fiber size and diameter is evident. Due to the nonwoven structure of these nanofibers themselves, the overall tensile strength of this separator in both the machine and cross directions is quite low (although it is nearly uniform in both directions). Thus, such a material could be processed uniformly if used in a battery cell, although the overall strength itself presents another challenge that manufacturers must face. In contrast, the separator of FIG. 1 exhibits channels due to the creation of pores in the same direction (i.e., by extruding the film in one direction), and exhibits extremely high longitudinal tensile strength, but unfortunately the lateral tensile strength of this material is virtually nonexistent, making it, as previously mentioned, an extremely difficult and highly questionable battery separator material for practical use in a battery manufacturing environment.

[0030] The materials of the present invention, shown in the form of photomicrographs in Figures 3 and 4, are of a completely different structure than these two prior art products. One possibly preferred embodiment of the initial microfiber / nanofiber combination is EFTEC® A-010-4 fibrillated polyacrylonitrile fiber, which has a high population of nanofibers and microfibers (fibers and fabrics made therefrom have not been used as battery separator materials in the past). The resulting nanofibers present in such combinations are residuals resulting from the fibrillation of the initial microfibers. Nonwoven sheets made with these materials are shown in Figures 3 and 4. By way of example, these fibers can be used as a base material to which additional microfibers or additional nanofibers can be added as a means of controlling the pore size and other properties of the nonwoven, or such materials may be used as nonwoven battery separators themselves. Examples of such sheets with additional microfibers added are shown in Figures 5, 6 and 7. Typical properties of acrylic microfibers / nanofibers are shown below.

[0031] [Table 1]

[0032] As previously mentioned, these fibers are actually present in pulp-like compositions and therefore can be easily incorporated into wet-laid nonwoven manufacturing systems. EXAMPLES

[0033] Nonwoven fabric manufacturing method The material combinations were then weighed out to give different concentrations of both components before being introduced together into the wet-laid manufacturing process. Handsheets were prepared according to TAPPI test method T-205, which is incorporated herein by reference. Essentially, as previously described, very high aqueous solvent concentration formulations were mixed together under high shear conditions (typically used in wet-laid manufacturing and described as "refining" the fibers), and finally the wet structure was placed on a flat surface to allow the solvent to evaporate). Several different combinations were made to form the final nonwoven structure. In this process, only adjustments were made to the weights of the various main components by adjusting the initial amount of material included in each sheet. The materials and ratios are shown in Table 2.

[0034] Figures 5, 6 and 7 together correlate in structure to Example 3 below. The similarity of structure (large microfibers and small nanofibers) is evident from these micrographs, as well as the presence of smaller amounts of nanofibers within these structures.

[0035] The thickness of the fabric was measured and then cut to the appropriate size and shape for incorporation into a lithium ion rechargeable battery cell. However, prior to such incorporation, samples of the battery separator fabric were analyzed for various properties and tested for their potential as suitable battery separators. Additionally, comparative studies were performed on the battery separator nanofiber membrane of U.S. Patent No. 7,112,389, which is incorporated herein by reference, as well as battery separator films from Celgard. Comparative examples are reported from tests in that patent and from Celgard's product literature.

[0036] Working Example Examples 1-21 were produced in accordance with TAPPI Test Method T-205 using Engineered Fiber Technologies' EFTEC® A-010-04 fibrillated acrylic fiber (a combination of microfibers and nanofibers) (referred to as the "Base Fabric") and Fiber Visions T426 fiber (2 denier per filament, cut to 5 mm length) and bicomponent fiber made of polypropylene and polyethylene having a diameter of about 17 microns (referred to as the "Added Fiber"). The amount of fiber, conditioned basis weight, caliper, apparent density and porosity for each of the examples are shown in Table 2. The conditioned basis weight, caliper, apparent density and porosity were determined according to TAPPI T-220, which is incorporated herein by reference. The test was carried out according to the following:

[0037] [Table 2]

[0038] The higher the porosity, the greater the peak power in the battery. This high level of result would theoretically result in at least a reduction in the number of batteries required to provide the required power level to drive a particular device (e.g., an automobile) due to the increased power available from each individual battery. Such benefits would also be enhanced by an effective air resistance barrier. The porosity of the separators of the present invention can also be controlled by the ratio of nanofiber to microfiber, the type of nanofiber, and post-processing such as calendaring, as will be demonstrated below.

[0039] Battery Separator Substrate Analysis and Testing The test procedure was as follows.

[0040] Porosity was calculated according to the method in U.S. Patent No. 7,112,389, which is incorporated herein by reference. Results are reported as a percentage, which corresponds to the portion of the bulk of the separator that is filled with air or non-solid material (e.g., electrolyte) when in a battery.

[0041] Gurley according to TAPPI test method T460, which is incorporated herein by reference. The air resistance was tested. The equipment used for this test was a Gurley Densometer Model 4110. To perform the test, the sample was inserted and secured in the densometer. The cylinder gradient was raised to the 100 cc (100 ml) line and then allowed to drip under its own weight. The time (in seconds) it took for 100 cc of air to pass through the sample was recorded. Results are reported in seconds / 100 cc, which is the time it takes for 100 cubic centimeters of air to pass through the separator.

[0042] Mean flow pore size was tested according to ASTM E-1294 "Standard Test Method for Pore Size Characterization of Membrane Filters Using Automated Liquid Porosimetry," which uses an automated bubble point method using a capillary flow porosimeter per ASTM F 316. Testing was performed by Porous Materials, Inc. (Ithaca, NY).

[0043] The air permeability of a separator is the length of time it takes for a given volume of air to flow through a standard area under slight pressure. The procedure is described in ASTM D-726-58.

[0044] The tensile properties, Gurley air resistance and mean flow pore size are shown in Table 3.

[0045] [Table 3]

[0046] Thus, the examples of the present invention show a very small average pore size, which indicates that multiple recharging cycles for the battery are possible. Furthermore, it has been shown that the pore size can be controlled by changing the ratio of nanofiber material to microfiber material, thereby changing the pore size. This is a significant advantage that does not exist in any of the prior art, and therefore, with this technology, the pore size can be tailored by the battery manufacturer according to the end user's requirements. Thus, the separator can be designed for power tool or automotive applications to have different properties than rechargeable watch batteries, cell phones, or laptop computers.

[0047] The tensile properties in the examples given are isotropic, i.e., the same in all directions, with no difference between the machine and cross directions. Comparative examples show tensile properties that differ considerably between the tensile strength in the machine direction (MD) and the cross direction (CD). In general, nanofiber-based battery separators are very weak. Thus, one advantage of the present invention is the tensile strength, which allows for rapid processing in the manufacture of batteries, tight winding of the batteries, and high durability in the use of the batteries. Such MD tensile strength is preferably greater than 250 kg / cm2, more preferably greater than 500 kg / cm2, and most preferably greater than 1000 kg / cm2. The requirements for the CD tensile strength are much smaller, preferably greater than 100 kg / cm2, more preferably greater than 250 kg / cm2, and most preferably greater than 500 kg / cm2.

[0048] As previously noted, calendaring and increasing the population of nanofibers relative to microfibers reduces the overall average pore size, again demonstrating the ability of the present technology to target specific dimensions on demand.

[0049] To demonstrate the state of the art, test results for two comparative examples are presented. The first comparative example (CE1) is an example of electrospun nanofibers in US Patent No. 7,112,389, in which Example 4 is taken as a typical example for comparison purposes. The second comparative example (CE2) is a Celgard 2325 membrane separator. Test results are from the manufacturer, Polypore, and are reported in the literature for their products. The reported results for these materials are shown in Table 4 below.

[0050] [Table 4]

[0051] The isotropic properties of the separator of the present invention show the potential for making thinner materials without sacrificing strength in either direction. Such a result would allow for lighter, thinner, and cheaper batteries with greater amounts of electrolyte present, and perhaps even greater electrode surface area for improved power production. Additionally, when the electrodes of a battery are pressed together, tensile strength is required to prevent the electrodes from touching. The tensile strength of CE2 is high in the machine direction (MD), but very low in the cross direction (CD). The MD tensile strength of CE1 is very low and no CD is reported, limiting the usefulness of the overall product from a manufacturing and processing standpoint.

[0052] The lower the air resistance, the greater the available and usable power in the battery and the less energy loss during recharging. Also, the lower the air resistance, the lower the thermal impact on the whole battery. The examples of the present invention show relatively low results compared to the comparative examples, especially the comparative example CE2. However, the comparative example CE1 has a very low combination of porosity and pore size, and also a low combination of the above-mentioned tensile strength, and the shortcomings of such a battery separator are obvious. The technology of the present invention provides an overall good effect from all points of view. In addition, with the control of the thickness and the amount of nanofibers present in the entire fabric structure, the air resistance of the separator of the present invention can be modified to a low level that is consistent with the material of CE1, and it is further evident that the results obtained by the technology of the present invention employed here are unexpectedly good and beneficial.

[0053] Battery separator thicknesses range from 15 microns to over 100 microns. With high strength, 12 gsm sheets appear to be able to be produced without difficulty, and the thickness can be reduced by calendaring, so that a full range of useful sheet thicknesses can be achieved using this technique. For example, a 12 gsm sheet would have half the thickness of a sheet produced at 25 gsm (i.e., about 40 microns). Calendering or compressing the sheet can reduce this thickness by 50%, resulting in a thickness of 20 microns. With improvements in compression, thinner sheets can be produced, and even thinner sheets can be compressed, all of which would be within the scope of the present invention.

[0054] Battery configuration and actual battery test results FIG. 8 shows one possible embodiment of a battery 10 of the present invention including a separator 18 of the present invention therein. The battery cell 10 includes a housing 12 within which all other components reside and which is tightly sealed to prevent environmental contamination and leakage of electrolyte from the cell. An anode 14 is mounted in tandem with a cathode 16, with at least one battery separator 18 between the two. An anode lead 20 is attached to the anode 14, while a cathode lead 22 is attached to the cathode 16. The anode 14 is housed within an anode container 24, while the cathode is housed within a cathode cover 26. Insulators 28 are present to separate the anode 14 and cathode 16 from touching the housing 12 as well as the anode container 24 and cathode cover 26. The cathode cover 26 includes a safety vent 30, and a gasket 32 ​​is present to allow pressure to be applied within the cell 10. Finally, a thermistor 34 is present around the inner periphery of the housing 12. A liquid electrolyte is added to the cell prior to sealing to provide the necessary ion production. Thus, the separator 18 helps prevent contact between the anode 14 and the cathode 16 while allowing selected ions produced from the electrolyte to migrate through the electrolyte. A typical configuration of a battery cell is described as such, however, depending on the size and configuration of the battery cell itself, configurations of size and shape for each internal component may vary. In this context, coin cell batteries of substantially circular solid components were fabricated to perform suitable testing of the effectiveness of separators in such cells.

[0055] For this purpose, the electrical properties of the separator were first tested by fabricating symmetric lithium foil-separator-lithium foil 2016 coin cells and testing them for electrical resistance, and then fabricating asymmetric carbon electrode-separator-lithium foil 2016 coin cells. Testing was performed in the Nanotechnology Laboratory at the Georgia Institute of Technology School of Materials Science and Engineering. For the symmetric lithium-separator-lithium 2016 coin cells, 5 / 8 inch rounds were cut from the selected separators and placed in an argon-filled glove box. It was dried in a vacuum chamber at 70° C. for about 12 hours and then incorporated into the following: (a) A symmetric lithium foil-separator-lithium foil 2016 coin cell, and (b) Asymmetric carbon electrode-separator-lithium foil 2016 coin cell.

[0056] The electrolyte used was 1M LiPF6 in an EC:DMC:DEC mixture (1:1:1 by volume). The lithium foil was rolled to a thickness of 0.45 mm, and one or two layers of separator were used in this study. Celgard 2325 separator, CE2, was the specific comparative example for similar tests.

[0057] After storage for two days, potentiostatic electrochemical impedance spectroscopy (EIS) measurements were performed on each of the assembled two-electrode Li-separator-Li coin cells in the frequency range from 0.01 Hz to 100 kHz.

[0058] Each cell contained the following contributors to the total resistance: (i) Li-ion transport in the electrolyte / separator; (ii) Li-ion transport in the solid-electrolyte interfacial layer (SEI layer) for each Li electrode; and (iii) electron transport at the Li cell contacts. Among these contributors to the resistance, (iii) electron transport can generally be neglected, while (i) Li-ion transport in the electrolyte usually does not give a semicircle in this frequency range due to their high characteristic frequency.

[0059] Since we are primarily interested in (i) the transport of Li ions in the electrolyte / separator, we focused on the high frequency range of the relevant Nyquist plots. The total resistance for the transport of ions through the separator was close to the real value of the total resistance Z at high frequencies, where the imaginary component of the complex impedance becomes zero. As mentioned before, the electrical resistances of the interfaces and electrodes are much smaller than the ionic resistance and can therefore be neglected.

[0060] The results of the AC EIS analysis are summarized in Table 5 below. The ionic resistance is the resistance of the electrolyte in the separator, which is calculated from the formula Ri=I×A / t, where Ri is the ionic impedance, I is the impedance in ohms, A is the area of ​​the cell in square centimeters, and t is the thickness of the separator in centimeters. As can be seen, the ionic impedance of the cell can be reduced by more than 70% by using the appropriate combination of microfibers and nanofibers, as shown by the monolayer in Example 19. Furthermore, by selecting the appropriate combination, the impedance can be tuned to any value within a wide range of impedances. This ability to tune such properties is a significant advantage of the present invention.

[0061] [Table 5]

[0062] The ionic resistance of the separator / electrolyte layers ranged from 2 to 6 ohms per layer, and a comparative study showed that Examples 18 and 19 were very close to the values ​​of CE2, a Celgard 2325 separator.

[0063] For the asymmetric carbon electrode-separator-lithium foil 2016 coin cell, the carbon electrode is based on Pureblack® carbon and carboxymethylcellulose (CMC) binder. The composition of the electrodes was: Pureblack®-88.85 wt%, CMC (MM 250 kDa, DS 0.9)-11.15 wt%. Before assembling the cells, the electrodes were dried in vacuum at 100°C for two days. The same type of electrolyte used above (1M LiPF6 in EC:DMC:DEC mixture (1:1:1 by volume)) was also used here. The results of the first Li insertion and extraction cycles collected at a slow rate of C / 20 are shown below in Table 6.

[0064] [Table 6]

[0065] The capacity and coulombic efficiency of the electrodes on the first cycle are similar for cells containing Examples 18, 12 and Celgard separator CE2. Then, at moderate rates, the separator of the present invention shows effective results, similar to the anisotropic Celgard material. However, a 15% increase was actually observed with Example 34, which is far greater than expected for the performance of such a separator. Thus, the materials of the present invention generally either approach or exceed the performance of the current industry standards.

[0066] It should be understood that those skilled in the art may make various modifications within the scope of the present invention without departing from the spirit of the invention. It is therefore intended that the present invention be defined by the appended claims as broadly as permitted by the prior art and, if necessary, in view of the specification. This specification includes the disclosure of the following inventions. [1] A polymeric battery separator comprising a nonwoven blend of microfibers and nanofibers, wherein a single layer of the separator provides sufficient porosity for the passage of electrolyte ions and adequate protection against electrode contact through the single layer of the nonwoven blend. [2] The battery separator of [1], comprising a single layer of fibers, said layer including both nanofibers and microfibers, said nanofibers having an average diameter of less than 1000 nm and said microfibers having a diameter of greater than 3000 nm, and said nanofibers and microfibers being intermingled, whereby at least a portion of the nanofibers reside in the interstices between the microfibers. [3] The separator has a machine direction (MD) tensile strength greater than 250 kg / cm2. The battery separator according to [1]. [4] The battery separator of [3], wherein the separator has a machine direction (MD) tensile strength greater than 500 kg / cm2. [5] The separator has a cross direction (CD) tensile strength greater than 100 kg / cm2. The battery separator according to [1]. [6] The separator has a cross direction (CD) tensile strength greater than 250 kg / cm2. [5] The battery separator according to [5]. [7] The battery separator of [1], wherein the nanofibers exhibit a transverse aspect ratio greater than 1.5:1. [8] The battery separator of [1], comprising nanofibers that form islands-in-the-sea. [9] The mean flow pore size is less than 2000 nm. [1 ] A battery separator as described in

[10] The battery separator of [1], having a thickness of less than 250 microns.

[11] The battery separator of

[10] , having a thickness of less than 100 microns.

[12] The battery separator of [2], wherein the separator has a machine direction (MD) tensile strength greater than 250 kg / cm2.

[13] The battery separator of [2], wherein the separator has a cross direction (CD) tensile strength greater than 100 kg / cm2.

[14] The battery separator of [2], wherein the nanofibers exhibit a transverse aspect ratio greater than 1.5:1.

[15] The mean flow pore size is less than 2000 nm. 3. The battery separator according to claim 2.

[16] The battery separator of claim 2, having a thickness of less than 250 microns.

[17] The battery separator of [1], wherein the separator is isotropic with respect to tensile strength in the longitudinal and transverse directions, and the separator has a longitudinal tensile strength greater than 250 kg / cm2.

[18] A battery, capacitor, supercapacitor or ultracapacitor comprising the battery separator according to [1].

[19]

[18] A method of generating electricity by using a battery.

[20] A method for producing a monolayer polymeric battery separator, the method comprising the steps of: providing a first slurry of polymer microfibers and nanofibers; subjecting the slurry to a high shear wet-laid nonwoven fabrication process, thereby entangling the nanofibers with the microfibers to form a single layer nonwoven fabric; wherein the nonwoven fabric exhibits an average pore size that determines the amount of nanofibers that are introduced into the initial slurry prior to forming the nonwoven fabric.

[21] The method of

[20] , wherein the microfibers and nanofibers present in the initial slurry are the product of a fibrillation process that removes nanofibers from the microfibers.

[22] The method of

[21] , comprising the additional step of introducing second fibers selected from the group consisting of polymeric microfibers, polymeric nanofibers, and mixtures or combinations thereof, into the first slurry prior to subjecting the first slurry to the wet-laid nonwoven fabrication process, wherein such addition of second fibers alters the mean flow pore size of the resulting nonwoven fabric compared to the properties of a nonwoven fabric produced by carrying out the nonwoven fabrication process according to the same manufacturing conditions without the use of second fibers. [Explanation of symbols]

[0067] 10 battery cell, 12 housing, 14 anode, 16 cathode, 18 separator, 20 anode conductor, 22 cathode conductor, 24 anode can, 26 cathode cover, 28 insulator, 30 safety vent, 32 gasket, 34 thermistor.

Claims

1. 1. A method for making a monolayer polymeric battery separator, the method comprising the steps of: Providing a first slurry of polymer microfibers and nanofibers; subjecting the slurry to a high shear wet-laid nonwoven fabrication process, thereby entangling the nanofibers with the microfibers to form a single layer nonwoven fabric; wherein the nanofibers have an average diameter of less than 1000 nm and the microfibers have a diameter of greater than 3000 nm, and the nonwoven fabric exhibits an average pore size based on the amount of nanofibers introduced into the initial slurry prior to forming the nonwoven fabric.

2. 10. The method of claim 1, wherein the microfibers and nanofibers present in the initial slurry are the product of a fibrillation process that removes nanofibers from the microfibers.

3. 3. The method of claim 2, comprising the additional step of introducing second fibers selected from the group consisting of polymeric microfibers, polymeric nanofibers, and mixtures or combinations thereof, into said initial slurry prior to subjecting said initial slurry to said wet-laid nonwoven fabrication process, wherein such addition of second fibers alters the mean flow pore size of the resulting nonwoven fabric compared to the properties of a nonwoven fabric produced by carrying out said nonwoven fabric fabrication process according to the same manufacturing conditions without the use of second fibers.

Citation Information

Patent Citations

  • Aramid tissue material and electrical and electronic part using the same

    JP2005307360A

  • Separator for electric storage device

    JP2010098074A

  • Power storage device separator

    JP2010129308A

  • Separator for non-aqueous batteries, non-aqueous battery using same, and production method for separator for non-aqueous batteries

    WO2011033975A1